Morphological and molecular characterization of potato cyst nematode populations from The Nilgiris - BAIRWA, AARTI; P, VENKATASALAM E; A, JEEVALATHA; M, PRIYANK H; BUCKSETH, TANUJA; A, JENIFER; SHARMA, SANJEEV; SINGH, R K; CHAKRABARTI, S K (The Indian Journal of Agricultural Sciences, 2020)
Quarantine species of potato cyst nematodes (PCN), Globodera rostochiensis and G. pallida, were reported from Nilgiris during 1961. The studies were carried out at ICAR-CPRS, Muthorai, Ooty and ICAR-CPRI, Shimla during 2015–17. To investigate the distribution of PCN, soil samples were collected from potato growing areas of Nilgiris and were identified based on morphological criteria and ITS-1 region. Molecular characterization using ITS-1 region specific primers revealed the presence of pure population of G. rostochiensis in 50% of the samples, G. pallida in 10.7% of the samples, mixed population in 28.6% of the samples and absence of both the species in 10.7% of the samples. The phylogenetic analysis inferred by the sequence of the ITS-1 region confirmed 92–100% genetic similarities in Globodera spp. Seventeen isolates of G. rostochiensis showed 92–99% genetic similarity and rest four 92–100% similarities. Whereas, genetic similarity among the ten isolates of G. pallida was 96.1–99.4%. In the morphometric characters J2s of G. rostochiensis exhibited shorter body length (459.8 μm) than G. pallida (493.7 μm). G. rostochiensis and G. pallida had difference in mean stylet length (21.1 μm and 23.4 μm respectively), hyaline tail terminal length (28.3 μm and 24.2 μm respectively) and shape of stylet knob. Highest mean value of vulval basin-anus distance (65.3 μm), number of cuticular ridges between vulval basin-anus (18.4) and Granek’s ratio (4.0 μm) was recorded in G. rostochiensis than G. pallida. Therefore, the present study will help to take appropriate and region specific PCN management decisions according to species dominance in that area.